China into Africa trade, aid, and influence - Rotberg, Robert I. (Brookings Institution Press, 2008)
"Discusses the evolving symbiosis between Africa and China and specifies its likely implications. Among the specific topics tackled here are China's interest in African oil, military and security relations, the influx and goals of Chinese aid to sub-Saharan Africa, human rights issues, and China's overall strategy in the region"--Provided by publisher.